Population Dynamics of Yellow Prawn (Metapenaeus monoceros) Captured at Night in the Waters of Samboja Kuala, Kutai Kartanegara Regency - Pradana, Rizki Tio; Syahrir R, Muhammad; Abdunnur, Abdunnur (Nusantara Tropical Fisheries Science (Ilmu Perikanan Tropis Nusantara), 2023)
Samboja Kuala is one of the Kelurahan in Samboja District which is an area where most of the population works as fishermen.  There are two types of fishery activities in the Samboja Kuala area, namely capture fisheries (fishermen) and aquaculture fisheries. One of the most common catches obtained by fishermen is shrimp.  Yellow-spotted shrimp (Metapenaeus monoceros) is one of the catches of fishermen shrimp in Samboja Kuala Waters.  This study aims to determine several parameters of population dynamics using the carapace length data frequency method.  The research was conducted in Samboja Kuala waters, Kutai Kartanegara Regency, in November-December 2022.  Based on the results of the study, the sex ratio between males and females was 0,38: 2,65.  The length range in male and female sex is 48,34 mm – 78,85 mm and 48,80 mm – 90,78 mm.  And the natural mortality (M) of males and females was 1,27 per year and 1,65 per year, the capture mortality (F) of males and females was 0,63 per year and 1,64 per year, the total mortality of males and females was 1,90 per year and 3,29 per year, and the exploitation rates of males and females were 0,33 and 0,50.  New additions of males occurred in October by 16,27% and new additions of females occurred in October by 24,93%.  And it is known that the yield per recruitment value is 0.04 grams / recruitment.